A formação e a atuação profissional de licenciados em música: um estudo na UFSM - Xisto, Caroline Pozzobon (2004)
This investigation corresponds to the Art and Education Area of the PPGE/UFSM. It aimed at establishing a connection between graduate Artistic Education- Degree in teaching to elementary and high school with mayor in music and Music Full Degree of UFSM, students academic experiences and the needs found in a variety of different of professional development. Along the development of this study, some references are presented in order to guide it, including questionings on recent discussions about the connection between the teachers development and their performance in class, such as dichotomy between theory and practice during graduation and the study about different stages of their teaching careers conducted by Huberman (1995) and the characterization and constitution of teaching knowledge according to Tardif (2002). The context of music teacher development is presented through the characterization of the graduates development in two music teacher development models of this University and of the analysis of the present situation of reformulation in which Brazilian music teachers development courses go through. Afterwards, the methodology conception used in the research development is described as well as the criteria for selecting the participating subjects and the procedures for data collection and analysis. A small survey was carried on with 16(sixteen) graduates from the two music teacher development models of UFSM. The data was collected trough questionnaires and semi-structured interviews. The data was analyzed through a qualitative and quantitative approach and are presented and discussed in three categories: (1) Music teachers development; (2) Music teachers performance; (3) connection between music teachers development and performance. In the conclusion there are some contributions of this investigation to the area of musical education relating to teachers development. Through the graduates statements, it was possible to investigate, from their own perspective, the relationship established between the academic education and the professional performance in the multiple areas of activity where musical education takes place. The areas of activity of these graduates were identified and their professional activities where mapped. It was made an analysis of the relationship established between the teaching knowledge for the constitution of the pedagogical practice of the investigated music teachers. Yet, according to the interviewees point of view, it was verified to what extent the academic education is related to the professional market demand and the needs of the areas where these music teachers work. At last, some suggestions for future researches are given.